2019
DOI: 10.3346/jkms.2019.34.e213
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Prevalence, Intensity and the Number of Workers Exposed to Cigarette Smoking across Occupations and Industries in Korea

Abstract: Background Tobacco smoking affects the incidence of various illnesses such as lung cancer, respiratory diseases, and cardiovascular diseases. In an effort to prevent smoking-related cancers, we aimed to estimate the smoking prevalence, intensity, and number of workers exposed to smoking, which would be specific to the occupational and industrial circumstances in Korea. Methods We used the Korean Working Condition Survey (KWCS) and Korea's Census data. Smoking prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Furthermore, cigarette consumption was higher by about 15.8% and 11.7% in those with freelancing jobs and employees due to occupational pressures, as well as more stress and anxiety, when compared with unemployed women and housewives. Jung et al in South Korea also observed similar results when analyzing the relationship between job and cigarette consumption (27). In this research, housewives, in comparison to other occupations, also consumed 33% more waterpipe.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, cigarette consumption was higher by about 15.8% and 11.7% in those with freelancing jobs and employees due to occupational pressures, as well as more stress and anxiety, when compared with unemployed women and housewives. Jung et al in South Korea also observed similar results when analyzing the relationship between job and cigarette consumption (27). In this research, housewives, in comparison to other occupations, also consumed 33% more waterpipe.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, most of the students in this study worked at a motor vehicle factory (or in similar industries) because they joined the cooperative education that was offered by the vocational school. They are therefore likely to imitate the smoking behavior of their colleagues and peers to seek recognition, a notion supported by research that revealed the occupations and industries that most affect smoking prevalence (Jung et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…First, we did not adjust for important confounding factors such as smoking and drinking due to lack of information. Nevertheless, a recent study by Jung et al that analyzed the smoking status of Korean workers provides a glimpse into the confounding effect of smoking on the association between respiratory tract cancer and industrial groups [ 48 ]. According to the study, in male workers, the prevalence of smoking was higher among the workers in the fishing, mining, and construction industries than that of overall male workers.…”
Section: Discussionmentioning
confidence: 99%